User Errors: Reason, (Xeno)-Feminism and the Political Insufficiency of Ontology - Woodard, Ben (Identities: Journal for Politics, Gender and Culture, 2020)
This paper revisits elements of second wave feminism—in its psychoanalytic, radical, materialist, Marxist and deconstructionist aspects—the better to understand how it is we might define sexual difference today. The vexed question of sexuation, of what it means to be a woman in particular has today generated great tensions at the theoretical, legal and philosophical level. This paper is an attempt to return to aspects of the second wave—an unfinished project where many enduring feminist concerns were for the first time thoroughly and metaphysically articulated—the better to defend the importance of sexual difference. To this end, the transcendental and parallax dimensions of sexed life will be discussed, alongside a defence of the centrality of the mother to our thinking about the relevance and necessity of preserving the importance of sexual difference, not only for thought but also for political and legal life. Author(s): Ben Woodard Title (English): User Errors: Reason, (Xeno)-Feminism and the Political Insufficiency of Ontology Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 17, No. 2-3 (Winter 2020) Publisher: Institute of Social Sciences and Humanities - Skopje Page Range: 54-68 Page Count: 15 Citation (English): Ben Woodard, “User Errors: Reason, (Xeno)-Feminism and the Political Insufficiency of Ontology,” Identities: Journal for Politics, Gender and Culture, Vol. 17, No. 2-3 (Winter 2020): 54-68. Author Biography Ben Woodard, Independent Researcher Ben Woodard is an independent scholar living in Germany. His work focuses on the relationship between naturalism and idealism during the long nineteenth century. He is currently preparing a monograph on the relation of naturalism and formalism in the life sciences. His book Schelling’s Naturalism was published in 2019 by Edinburgh University Press.